The counterterrorist manual a practical guide to elite international units - Thompson, Leroy, 1944- (Frontline, 2009)
Despite the significant and growing role of counter-terrorist units, little is known about the way they operate. The selection, training, structure, and principles of maintaining such units, together with basic theories of warfare, are the subject of Thompson's latest work.